The equivalent slab thickness of Mars' ionosphere: Implications for thermospheric temperature. Issue 9 (5th May 2015) - Mendillo, M.; Narvaez, C.; Lawler, G.; Kofman, W.; Mouginot, J.; Morgan, D.; Gurnett, D.
Abstract The total electron content (TEC) of a planetary ionosphere is dominated by plasma near and above the height of maximum electron density (Nmax). The ratio TEC/Nmax represents the thickness (τ) of a TEC slab of uniform density (Nmax). For a photochemical ionosphere, τ relates to the scale height (H = kT/mg) of the ionized neutral gas as τ ~ 4 × H. Derived temperatures refer to ~160 km in thermosphere height—below the asymptotic temperature of the exosphere. The MARSIS instrument on Mars Express has produced data sets of TEC and Nmax. We used them to form τ patterns versus solar zenith angle and solar cycle phase. For daytime (SZA < 90°) conditions, <τ > day ~ 50 km, decreasing rapidly for solar zenith angle (SZA) > 90° to < τ > night ~ 25 km. These correspond to Tn values of 250°K and 125°K. Using Mars Global Surveyor data, τ patterns show a mild dependence upon the solar EUV flux proxy F10.7, with ΔTn(°K) ~ 0.3° per unit change in F10.7 at Mars.